AB0264 Trend in hospital admissions in rheumatoid arthritis in spain: a national observational cohort study (1999–2015) (trend-ar study). (12th June 2018) - Espinosa Malpartida, M.; Barbadillo, C.; Godoy, H.; Martínez Prada, C.; Villaverde, V.; Morado Quinoa, C.; Quirós, J.; Perez-Fernandez, E.; Peña, M.; Macía Villa, C.; García-Vadillo, A.; Crespi, N.; et al.
Abstract : Background: There have been significant changes in the management of rheumatoid arthritis (RA) during the past 20 years. The potential impact of these strategies on hospitalisation trend is unknown. Objectives: To analyse the incidence and trend of hospital admissions in patients with RA in Spain from 1999 to 2015. Methods: This is a population based study. We analysed a national administrative database that includes a Minimum Basic Data Set (MBDS) of hospital admissions of patients with RA during the period 1999–2015. The admission cases in patients with RA were identified by the presence in primary and secondary diagnosis of the ICD9 codes (714.0–714.9). The population at risk was estimated through the population census of the National Institute of Statistics, with an estimated prevalence for RA of 0.5%, with crudes and adjusted admission rates being calculated. The trend was analysed using Generalised Linear Models (GLM). Results: There were a total of 3 38 343 hospital admissions in RA patients during the study period, accounting for a total of 1 76 097 patients (1 17 985 women and 58 112 men). The mean age at admission was 68 years (67.8 in women and 68.5 in men), with a linear increase throughout the study period from 65.3 in 1999 until 70.5 in 2015 (p<0.001). The main admission code was for Osteoarticular and connective tissue diseases (20%) followed by Circulatory system diseases (16.8%). There were a total of 18 641 intrahospital deaths (5.5% of all the admissions). The age-adjusted admission rate was 12.03/100 RA patients*yr (9, 12 for women and 1.88 for men). The age-adjusted admission rate increased from 1999 to 2015 (in both genders). An annual increase of admission rate of 3.7% is estimated. When adjusting by age, the largest increase is observed in patients older than 80 years, with an estimated annual increase of 7.5%. Conclusions: In Spain, despite the improvement in RA management, there is a global tendency to the increase of admissions during the period of 1999–2015, mainly in >60 year, especially in >80 year. Disclosure of Interest: None declared